Effect of set retarder on the hydratation mechanism and microestructure of plaster of Paris - Hincapie, Angela Maria (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
The objective of this work was to evaluate the effect of set retarding chemicals on plaster of Paris hydration and microstructure. Contents added were 0,03% citric acid, 0,8% caseyne and 1,5% gelatine. The evolution of the hydration was followed by calorimetry measurement and the microstruture ibserved by scanning electron microscope. The results show that the effect of these retarders can be classified into two groups: 1) the first one, composed of citric acid and borax, affects the induction period, but not the reaction rate; 2) the second one, composed of caseune and gelatine, affects both the induction period and and the rate of hydration. No significant change in the shape of crystals was observed; with borax the crystals have a hexagonal but irregular shape. With the addition of gelatyne, the crystals are thick, rounded and smaller than the crystals formed with no retarder added.